FORMULASI SEDIAAN KRIM DEODORANT EKSTRAK ETANOL DAUN BELUNTAS (Plucea indica Less.) SEBAGAI PENCEGAH BAU BADAN - Eka Margaret Sinaga; Supartiningsih Supartiningsih; Siti Maimunah; Nikmat Jayadi (Jurnal Farmanesia, 2020)
Beluntas is one of the plants that is often used as traditional medicine. Beluntas leaves have antimicrobial activity against various kinds of bacteria. This study aims to formulate Beluntas leaf extract (Plucea indica Less.) in the form of a deodorant cream that functions as a deterrent to body odor. The research method was carried out experimentally which included extract preparation, formulation using Beluntas leaf extract (Plucea indica Less.) with a concentration of 5%, 7.5%, 10%, preparation quality test, and hedonic test. The results of the formula The deodorant cream preparation can be used properly and can prevent sweating for 8 hours and the deodorant cream does not cause irritation and provides comfort when used, from formulas 1, 2, and 3, all the results are good to prevent sweating in the armpits but, the formula favored by the volunteers was formula 1 because the aroma was just right unlike formula 2, and formula 3 which had a slightly more pungent aroma, and similarly to the color in formula 1, the color was light green, unlike formula 2, and formula 3 which tended to be lighter in color. dark green. Beluntas leaf ethanol extract can be used to prevent body odor, and the extract can be used as a natural deodorant cream to prevent body odor.